The formation of grain quality in varieties and winter wheat selection lines depending on the phase of forced winter dormancy or its absence - Tyshchenko, V.; Kobylynska О. (Scientific Progress & Innovations, 2023)
Wheat is the most valuable and widespread grain food crop. Its value is determined, first of all, by a high nutritional value of grain. It contains protein and gluten, which determine its food, technological, and commercial advantages. Therefore, the problem of increase and stability in producing high-quality winter wheat grain has been and remains topical. The content of protein and gluten in winter wheat grain varies within wide limits depending on growing conditions. They are affected by a number of factors: geographical, soil and climatic conditions, weather conditions of the current year, preceding crops, application of nitrogen fertilizers, sowing time and seeding rate, soil tillage, fighting weeds and pests, harvesting time, after harvest ripening. The difficulty in solving the problem of winter wheat grain quality consists in the fact that its indicators considerably depend on climatic peculiarities of the region and weather conditions of the year. The study was conducted to determine qualitative indicators of varieties and selection lines of soft winter wheat and the impact of winter exogenous dormancy phase or its absence on the formation of protein and gluten content. The investigations were held during 2018–2021 in the experimental field of Poltava State Agrarian University (PSAU) and laboratory conditions. The varieties and selection lines of soft winter wheat bred in PSAU as well as the varieties of other selection establishments were the materials for the study. The direct dependence of grain quality of soft winter wheat varieties and selection lines on the phase of winter exogenous dormancy was observed, as it is formed depending on morpho-type peculiarities, the time of winter entering, and the time of spring re-vegetation. During the year without the phase of winter exogenous dormancy (2020), the tendency to decreasing grain qualitative indicators – protein and gluten – was observed. The obtained results are important in the selection process and can be used in producing and cultivating soft winter wheat varieties (Triticum aestivum L.).